Omni‐functional crystal: Advanced methods to characterize the composition and homogeneity of lithium niobate melts and crystals. Issue 4 (16th August 2022) - Chen, Kunfeng; Wu, Ji'an; Hu, Qianyu; Lu, Zheng; Sun, Xiangfei; Wang, Zhiqiang; Tang, Gongbin; Hu, Hui; Xue, Dongfeng
Abstract: Lithium niobate (LN) is a type of multifunctional dielectric and ferroelectric crystal that is widely used in acoustic, optical, and optoelectronic devices. The performance of pure and doped LN strongly depends on various factors, including its composition, microstructure, defects, domain, and homogeneity. The structure and composition homogeneity can affect both the chemical and physical properties of LN crystals, including their density, Curie temperature, refractive index, and piezoelectric and mechanical properties. In terms of practical demands, both the composition and microstructure characterizations these crystals must range from the nanometer scale up to the millimeter and wafer scales. Therefore, LN crystals require different characterization technologies when verifying their quality for various device applications. Optical, electrical, and acoustic technologies have been developed, including x‐ray diffraction, Raman spectroscopy, electron microscopy, and interferometry. To obtain detailed structural information, advanced sub‐nanometer technologies are required. For general industrial demands, fast and non‐destructive technologies are preferable. This review outlines the advanced methods used to characterize both the composition and homogeneity of LN melts and crystals from the micro‐ to wafer scale. Abstract : For optical, electrical, and acoustic device applications, the advanced characterization method for measuring composition, microstructure, defect, domain, homogeneity, Curie temperature, refractive index, piezoelectricity of LiNbO3 bulk crystal is needed.